2008
DOI: 10.1177/000348940811700306
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Clinical Significance of Epidermal Growth Factor Receptor and Type 1 Insulin-Like Growth Factor Receptor in Nasopharyngeal Carcinoma

Abstract: These findings demonstrate that both receptor proteins may play an important role in the invasion, metastasis, and recurrence of NPC. Both receptors are valuable markers for assessing the prognosis of NPC. Their expression at such high frequencies provides the basis of combined targeted therapy with specific pharmacologic inhibitors to enhance the effects of radiotherapy and chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 20 publications
(1 reference statement)
2
27
0
2
Order By: Relevance
“…It has been shown that NPC tumors express both EGFR and IGF1R, although it is not clear whether IGF1R expression is specifically upregulated in EBV-infected tumors (53)(54)(55). High expression of IGF1R has been correlated with poor NPC patient survival, and targeting NPC xenografts with PPP reduces tumor growth (53,56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that NPC tumors express both EGFR and IGF1R, although it is not clear whether IGF1R expression is specifically upregulated in EBV-infected tumors (53)(54)(55). High expression of IGF1R has been correlated with poor NPC patient survival, and targeting NPC xenografts with PPP reduces tumor growth (53,56).…”
Section: Discussionmentioning
confidence: 99%
“…High expression of IGF1R has been correlated with poor NPC patient survival, and targeting NPC xenografts with PPP reduces tumor growth (53,56). Additionally, preliminary data suggest that targeting both EGFR and IGF1R in NPC may be more beneficial than targeting either RTK individually (15,57).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we enrolled 15 eligible articles containing survival outcomes [11,[15][16][17][18]22,[24][25][26][27][28][29][30][31][32][33][34][35], among which two studies were written in Chinese [22,33], whereas the others were English articles. These eligible studies were published from 2002 to 2012.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…Studies [17,24,25,31] dealing with differentiated tumor samples yielded HRs [95% CI] for both OS and DFS/RFS/PFS. In this subgroup, EGFR showed no significant prognosis relevance to OS: 2.60 [0.85, 7.90], (I2 = 76%, P = 0.09); while DFS/ RFS/PFS was observably greatly related to EGFR: 2.38 [1.36, 3.55], (I2 = 40%, P < 0.00001), (Fig.…”
Section: Subgroup Analysismentioning
confidence: 99%
“…This lymphangiogenic activity may promote lymphatic spread, metastasis, and recurrence of malignant tumors. Increased expression of IGF-1R has been detected immunohistochemically in primary undifferentiated oropharyngeal and nasopharyngeal tumors as well as metastatic lymph nodes [68], and has been associated with poor prognosis, increased metastatic potential, and high recurrence rates (Table 1) [69]. On the other hand, down-regulation of IGFBP-3 has been found in patients with tongue carcinoma and significantly associated with shorter disease-specific survival [70].…”
Section: Other Factors Implicated In Lymphangiogenesismentioning
confidence: 99%